Influence of Planting Dates on Seedathip 1 Tomato Seed Quality Produced in Songkhla - Quanchit Santipracha (Agriculture and Natural Resources, 1992)
Tomato variety Seedathip 1 was planted at one month interval during January and June in 1989 at Plant Science. Department, Faculty of Natural Resources, Prince of Songkla University, Hai Yai Campus to evaluate the influence of planting dates on seed quality. The results showed that seed yield, standard germination, field emergence, speed of germination and seedling growth rate of the seed from January and February plantings were high while the seed from June and April plantings were low in quality. The seed quality was lowest at April planting because of high temperature and relative humidity which were unfavorable for tomato fruit set and seed development.